2020
DOI: 10.1111/rego.12306
|View full text |Cite
|
Sign up to set email alerts
|

Tariff liberalization and product standards: Regulatory chill and race to the bottom?

Abstract: Does tariff liberalization cause regulatory chill by putting downward pressure on health, safety, and environmental standards? Or does it cause a race to the top as governments seek to use standards as nontariff barriers to trade? There remains remarkably little empirical evidence to answer these long-debated questions. We seek to address this lack by analyzing annual country-by-industry data on notifications of changes in sanitary and phytosanitary standards by world trade organization members. Our results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, demographic, governance and environmental determinants appear to be even more important. Recent work by Aisbett and Silberberger (2020) Moore and Zanardi (2011) find evidence of substitution effects for heavy users of this instrument among developing countries, as well as evidence of retaliation and deflection effects as determinants of antidumping measures.…”
Section: Figure 2 / Ntms In Gatt/wto Negotiation Roundsmentioning
confidence: 99%
“…However, demographic, governance and environmental determinants appear to be even more important. Recent work by Aisbett and Silberberger (2020) Moore and Zanardi (2011) find evidence of substitution effects for heavy users of this instrument among developing countries, as well as evidence of retaliation and deflection effects as determinants of antidumping measures.…”
Section: Figure 2 / Ntms In Gatt/wto Negotiation Roundsmentioning
confidence: 99%
“…Apart from the general literature on international trade, while exploring the literature, researchers found numerous studies carried in the context of tariff and non-tariff barriers (Chemingui & Dessus, 2008;Cheong & Tang, 2018;Daly et al, 2000;DaSilva-Glasgow, 2020;Fugazza & Maur, 2008;Grundke & Moser, 2019;Imbruno, 2016;Jørgensen & Schröder, 2003;Juust et al, 2020;Knobel et al, 2019;Liu et al, 2019;Magee et al, 2019;Maguire, 2001;Manzoor et al, 2019;Niu et al, 2018;Okumura, 2015;Santeramo & Lamonaca, 2019;Schuenemann & Kerr, 2019;Soon & Thompson, 2020;Toshimitsu, 2008;Winchester, 2009). Aisbett and Silberberger (2020) found that countries where tariff liberalization is higher, producers can adopt relatively cheaper standard and perform at top of the list. Cambini and Soroush (2019) proposed a grid tariffs to account for costs under mechanism of net metering and concluded that employing a multi-part tariffs (variable component that imitates net effect on operating cost together with fixed component that imitates cyclical grid-connection cost of distribution networks) there is possibility to mitigate the snags of optimize prosumption and net metering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that countries receive more TBT concerns subsequent to applied tariff reductions, in particular in OECD countries. Aisbett and Silberberger (2020) argue instead that tariff reductions lead to more SPS notifications that a country reports to the WTO. However, none of these papers use the full available sample of SPS/TBT activity or juxtapose the impact of different tariff measures.…”
Section: Introductionmentioning
confidence: 96%
“…They find that TBT concerns are more frequent after applied tariff reductions, in particular in OECD countries. Considering products at the HS two‐digit level, Aisbett and Silberberger (2021) argue instead that bound tariff reductions lead to more SPS notifications of members to the relevant WTO committees, independent of any subsequent concerns by other countries. However, these papers make no attempt to distinguish theoretically or empirically between tariffs and tariff overhangs, and why this issue could be important.…”
Section: Introductionmentioning
confidence: 99%